Pengaruh Penerapan Sistem E-Filing Terhadap Kepatuhan Wajib Pajak Dengan Pemahaman Internet Sebagai Variabel Pemoderasi Pada Kpp Pratama Batam Utara - Dian Efriyenti (Global Financial Accounting Journal, 2018)
This study aims to analyze the influence of E-Filing System Implementation on Taxpayer Compliance with the Understanding of the Internet as Moderate Variables at KPP Pratama Batam Utara. The population of this research is Individual Taxpayer registered as Taxpayer in KPP Pratama Batam Utara. The sample used in this study were 100 respondents. The results of this study indicate that (1) Application of E-Filing System has a positive and significant impact on Taxpayer Compliance. Implementation of E-Filing System has a positive and significant impact on Taxpayer Compliance. This can be proved by a t value of 7.722 which is greater than t table 1.66039 with a significance value of 0.000 smaller than 0.05. Regression coefficient value of 0.615 which has a positive direction shows the better Application of E-Filing System then Taxpayer Compliance will also be good. (2) Understanding the Internet can moderate the influence of E-filing System Implementation on Taxpayer Compliance. It is proved through Moderated Regression Analysis which gives coefficient value equal to moderation variable (interaction between Application of E-Filing System and Internet Understanding) gives coefficient value 0,072 with significance 0,003. These three variables can be inferred have an effect on Taxpayer Compliance, because it has a level of significance below 0.05.